The effect of CO 2 laser irradiation on failed implant surfaces - Shibli, Jamil Awad; Theodoro, Letícia Helena [UNESP]; Haypek, Patricia; Garcia, Valdir Gouveia [UNESP]; Marcantonio Júnior, Elcio [UNESP] (Wolters Kluwer, 2004)
The aim of this investigation was to evaluate the cleaning effect of CO 2 on surface topography and composition of failed dental implant surfaces. Ten failed dental implants were retrieved from nine patients (mean age, 46.33 ± 5.81 years) as a result of early or late failure. The implants were divided into two parts: one side of the implant was irradiated with a CO 2 laser (test side), while the other side did not receive irradiation (control side). The CO 2 laser was operated at 1.2 W in a continuous wave for 40 seconds (40 J energy). The handpiece of the CO 2 laser was kept at a distance of 30 mm from the implant surface, resulting in a spot area of 0.031415 cm 2 (38.20 W/cm 2; 1559 J/cm 2) in scanning mode (cervical-apical). One unused dental implant was used as a negative control for both groups. All implant surfaces were examined by scanning electron mi croscopy (SEM) and energy-dispersive spectrometer x-ray (EDS) for element analysis. SEM showed that the surface of the test sides consisted of different degrees of organic residues, appearing mainly as dark stains similar to those observed on the control sides. None of the test surfaces presented alterations such as crater-like alterations, lava-like layers, or melting compared with the nonirradiated surfaces. Foreign elements such as carbon, oxygen, sodium, calcium, and aluminum were detected on both sides. These results suggest that CO 2 laser irradiation does not modify the implant surface, although the cleaning effect was not satisfactory.
Keywords: Co 2 laser; Dental implants; Failures; Peri-implantitis; Scanning Electron Microscopy (SEM); Titanium; aluminum; calcium; carbon; carbon dioxide; oxygen; sodium; adult; aged; clinical article; energy; female; human; irradiation; laser; male; scanning electron microscope; spectrometry; surface property; tooth implantation; topography; Adult; Aged; Carbon Dioxide; Dental Implantation, Endosseous; Dental Implants; Dental Restoration Failure; Device Removal; Electron Probe Microanalysis; Equipment Contamination; Female; Humans; Lasers; Male; Microscopy, Electron, Scanning; Middle Aged; Oxides; Surface Properties